Implementasi Program Kampus Mengajar Demi Meningkatkan Budaya Literasi Di SD Putra Wijaya 1 Surabaya - Yohana Fransiska Natalia (Jurnal Pelayanan Hubungan Masyarakat, 2023)
Education is an important factor in building a literacy-cultured society. In the current era, the culture of literacy in education has begun to be abandoned. Due to the existence of a program from the government, namely the Teaching Campus, it is hoped that it will be able to have a positive impact on the development of a cultural interest in literacy for students. The methods used in this activity include interviews, direct observation, and active participation. Campus Teaching activities are carried out in groups with 3-5 members from different universities and study programs according to placement. The purpose of this activity is to provide opportunities for students to practice their skills by studying outside the campus and developing themselves through activities outside the classroom. The results obtained from the implementation of the Teaching Campus program at Putra Wijaya 1 Surabaya Elementary School were an increase in literacy as seen from the results of the AKM score which had an increase compared to the initial test.